2017
DOI: 10.1016/j.ensci.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime induced neurotoxicity: A case series and review of the literature

Abstract: Cefepime is a fourth generation cephalosporin which is bactericidal for broad spectrum of organisms. This is a case-series of three patients who presented to our hospital with confusion secondary to cefepime use to treat urinary tract infection (UTI) and health care associated pneumonia (HCAP), after excluding other common etiologies of altered mental status (AMS). Of these three patients, one had progressive expressive aphasia and the other two demonstrated asynchronous myoclonic activity of the limbs. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The patients in this case series were identified prospectively by the authors, who were on EEG service at the times when the patients underwent EEG monitoring. 52/M 2 DZP ND ND 7 NCSE 11 7 39/F 6 DZP ND ND 5 NCSE 12 9 58/F 8 DZP ND ND 5 NCSE 13 9 68/F 4 DZP ND ND 5 NCSE 14 9 74/F 4 DZP, LEV ND ND 5 NCSE 15 4 74/F 7 PHE ND ND 3 NCSE 16 10 64/M 3 ND EP 17 11 57/F 10 LEV, PHE ND ND 4 NCSE 18 5 64/F 5 3 EP 19 12 68/M 7 CBZ 4 EP 20 12 85 Abbreviations: AMS, altered mental status; ASM, anti-seizure medication; CBZ, carbamazepine; CLN, clonazepam; DZP, diazepam; EEG, electroencephalogram; EP, encephalopathy; LEV, levetiracetam; LZP, lorazepam; NCSE, nonconvulsive status epilepticus; ND, not documented; PHE, phenytoin; VPA, valproate. a Patients were identified via a PubMed search for the terms "cefepime," "encephalopathy," "NCSE," and "non-convulsive status epilepticus."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients in this case series were identified prospectively by the authors, who were on EEG service at the times when the patients underwent EEG monitoring. 52/M 2 DZP ND ND 7 NCSE 11 7 39/F 6 DZP ND ND 5 NCSE 12 9 58/F 8 DZP ND ND 5 NCSE 13 9 68/F 4 DZP ND ND 5 NCSE 14 9 74/F 4 DZP, LEV ND ND 5 NCSE 15 4 74/F 7 PHE ND ND 3 NCSE 16 10 64/M 3 ND EP 17 11 57/F 10 LEV, PHE ND ND 4 NCSE 18 5 64/F 5 3 EP 19 12 68/M 7 CBZ 4 EP 20 12 85 Abbreviations: AMS, altered mental status; ASM, anti-seizure medication; CBZ, carbamazepine; CLN, clonazepam; DZP, diazepam; EEG, electroencephalogram; EP, encephalopathy; LEV, levetiracetam; LZP, lorazepam; NCSE, nonconvulsive status epilepticus; ND, not documented; PHE, phenytoin; VPA, valproate. a Patients were identified via a PubMed search for the terms "cefepime," "encephalopathy," "NCSE," and "non-convulsive status epilepticus."…”
Section: Discussionmentioning
confidence: 99%
“…2 Those with renal impairment are particularly at risk for these side effects, 3 although the same toxicities have been documented in patients without concurrent renal insufficiency. 4,5 A commonly reported constellation of symptoms is altered mentation with concurrent triphasic wave (TW) discharges on electroencephalogram (EEG). These reports have variably described the same electroclinical constellation of symptoms as either cefepime-induced encephalopathy or at other times cefepime-induced nonconvulsive status epilepticus (NCSE).…”
Section: Introductionmentioning
confidence: 99%
“…We noticed that 2–3 Hz GPD with a high negative component (above baseline) seemed to characterize cefepime‐induced encephalopathy in contrast to the triphasic waves induced by other illnesses, such as hepatic encephalitis or Creutzfeldt–Jakob disease . Moreover, the triphasic morphology with negative polarity in the dominant phase was perceived as differing from the ‘typical’ triphasic wave by clinicians (odds ratio: 0.09, 0.02–0.22), suggesting that the clinicians differentiated the Tri‐HNC from ‘typical’ triphasic wave; however, only a few studies have focused on this characteristic feature …”
Section: Discussionmentioning
confidence: 90%
“…Although it is still unclear when antibiotic‐associated altered mental status with GPD should be diagnosed as non‐convulsive status epilepticus, the characteristic clinical presentations in the present cases led the physicians to assume a psychological cause. Interestingly, previous reports suggested that aphasia was a diagnostic feature of CIE, and we hypothesized that palilalia was a mild sign of aphasia in patients with CIE. A previous study showed that memory formation, sensory processing, and pain were cognitive functions associated with GABAergic inhibition . Together with the evidence that cefepime acts as a GABA A receptor antagonist, the symptoms that the patients experienced can be summarized to be dysfunctions of GABAergic inhibition.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, according to Chaïbi et al , cefepime neurotoxicity may account for a higher risk of mortality when compared with other β-lactams (risk ratio: 1.26) 7 8. In rare cases, neurotoxicity occurs without renal dysfunction or with a theoretically appropriate renal dose adjustment 6 9 10. In 2012, the Adverse Event Reporting System database of the Food and Drug Administration (FDA) identified 59 cases of non-convulsive status epilepticus during cefepime administration from 1996 to 2012.…”
Section: Discussionmentioning
confidence: 99%